SDLC IMPLEMENTATION METHOD FOR MONTHLY REPORT PROCESSING DATA PROCESSING APPLICATIONS - Mustika, Mustika (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2020)
Application of Puskesmas Activity Reports (LB4) can assist Puskesmas staff in delivering or making information more quickly and efficiently. Because the old system in the manufacturing process is still manual, because the calculation of the number of visitors is still counted one by one and there are still frequent errors SDLC method is applied in making the application, the programming language used is Microsoft Visual Basic 6.0, supported by MySql database to improve the quality of information presentation report on the activities of LB4 Puskesmas Seputih Banyak. The method used is to use data collection methods, observations using the SDLC Method, while the application design uses a document flow chart, Data Flow Diagrams (DFD), Flow Diagrams (Flowcharts), Entity Relationship Diagrams (ERD). besides that it also uses the MySql database. The application can facilitate each officer in making LB4 reports that no longer use written documents, so that it is faster in distributing visitor data and also can count the number of visitors who come without having to count manually, because in the LB4 Report Application Design System for each section and has the number automatic data without counting one by one each part.